2018
DOI: 10.3390/ijms19103104
|View full text |Cite
|
Sign up to set email alerts
|

Danger-Associated Molecular Patterns (DAMPs): Molecular Triggers for Sterile Inflammation in the Liver

Abstract: Inflammatory liver diseases in the absence of pathogens such as intoxication by xenobiotics, cholestatic liver injury, hepatic ischemia-reperfusion injury (I/R), non-alcoholic steatohepatitis (NASH), or alcoholic liver disease (ALD) remain threatening conditions demanding specific therapeutic options. Caused by various different noxae, all these conditions have been recognized to be triggered by danger- or death-associated molecular patterns (DAMPs), discompartmentalized self-structures released by dying cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
105
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(108 citation statements)
references
References 123 publications
0
105
0
3
Order By: Relevance
“…Lipopolysaccharide (LPS) is an example of Gram-negative bacteria-derived PAMP that triggers KC activation by activation of toll-like receptor (TLR) 4 [49]. DAMPs, which comprise a number of molecules released by necrotic cells, can cause KC activation in various types of sterile liver injury through activation of TLR4 as well [50]. KCs activated by LPS [51] or DAMPs released by liver cells in response to acetaminophen-induced toxicity [52] secrete interleukin-(IL-) 18, a cytokine that induces interferon-gamma production by T cells [53] and, consequently, directs a type I immune response.…”
Section: Perivascular Cells In Liver Injurymentioning
confidence: 99%
“…Lipopolysaccharide (LPS) is an example of Gram-negative bacteria-derived PAMP that triggers KC activation by activation of toll-like receptor (TLR) 4 [49]. DAMPs, which comprise a number of molecules released by necrotic cells, can cause KC activation in various types of sterile liver injury through activation of TLR4 as well [50]. KCs activated by LPS [51] or DAMPs released by liver cells in response to acetaminophen-induced toxicity [52] secrete interleukin-(IL-) 18, a cytokine that induces interferon-gamma production by T cells [53] and, consequently, directs a type I immune response.…”
Section: Perivascular Cells In Liver Injurymentioning
confidence: 99%
“…15,16 Moreover, HMGB1 reportedly acts as an endogenous DAMP after being released by necrotic cells or actively secreted by macrophage/monocytes into the extracellular environment, thereby triggering and amplifying inflammatory processes. 17 In particular, we previously reported that HMGB1 is the major DAMP released from necroptotic enterocytes during intestinal I/R to induce an inflammatory response and subsequent intestinal damage. 18 Recent advances have revealed the intimate interplay between SIRS or sepsis-induced organ failure and cell death or cell dysfunction resulting from necrosis/necroptosis, 19,20 apoptosis, 21,22 and autophagy.…”
Section: Introductionmentioning
confidence: 98%
“…Inhibition of extracellular HMGB1 attenuates inflammation and confers protection in various inflammatory‐associated diseases, including sepsis, hepatitis, ischemic stroke, and liver I/R . Moreover, HMGB1 reportedly acts as an endogenous DAMP after being released by necrotic cells or actively secreted by macrophage/monocytes into the extracellular environment, thereby triggering and amplifying inflammatory processes . In particular, we previously reported that HMGB1 is the major DAMP released from necroptotic enterocytes during intestinal I/R to induce an inflammatory response and subsequent intestinal damage …”
Section: Introductionmentioning
confidence: 99%
“…Although reperfusion (the reintroduction of oxygenated blood to the organ or tissue) induces inflammation and injury, it is necessary for organ viability. Cellular injury that occurs during ischemia results in the release of ATP into the local extracellular environment, which is further exacerbated during reperfusion, where sudden reoxygenation and resulting production of reactive oxygen species cause further release of DAMPs including ATP . Although the length of ischemic organ preservation time is minimized to reduce damage at the time of engraftment, IRI has been shown to affect both acute and chronic graft survival …”
Section: Targeting Atp In Iri and Graft Preservationmentioning
confidence: 99%
“…Cellular injury that occurs during ischemia results in the release of ATP into the local extracellular environment, which is further exacerbated during reperfusion, where sudden reoxygenation and resulting production of reactive oxygen species cause further release of DAMPs including ATP. [8][9][10][11] Although the length of ischemic organ preservation time is minimized to reduce damage at the time of engraftment, IRI has been shown to affect both acute and chronic graft survival. 12,13 A number of recent studies have established that extracellular ATP accumulation and subsequent purinergic signaling are an important mediator of solid organ transplantation.…”
Section: Targ E Ting Atp In Iri and G R Af T Pr E S E Rvati O Nmentioning
confidence: 99%